Pathologies sociales dans une métropole au sud du Brésil: pour une approche multidimensionnelle des territoires urbains - Graziela Serroni Perosa; Cristiane Kerches da Silva Leite; Frédéric Lebaron; Francisco Fonseca (Confins)
This study intends to show the importance of multidimensional analyzes in the management of public policies related to urban territories. The Principal Components Analysis (PCA), based on the dimensions of the Social Health Index, allows to study economic and social disparities between the subprefectures of the city of São Paulo, based on data from the 2010 census, surpassing the simplification of the Development Index Human (HDI). The multi-dimensional articulation of social phenomena by the ACP operationalizes the concept of "social space" (Bourdieu) and provides a valuable diagnostic and impact tool for the study of public policies. It is possible to observe how the traditional indicators mask the nuances and the relative differences of the territories and their apparently homogeneous inequalities.